Mobile app glossary of terms in Islamic banking and finance (Arabic-Malay-English) via iOS and android based devices - Dollah, Nafi@Hanafi; Md Ghalib, Mohd. Feham; Sahrir, Muhammad Sabri; Hassan, Rusni; Omar, Zakaria; Zakaria, Abdul Wahab (2017)
The expansion of Islamic banking practices through various local financial institutions leads to the need in understanding the terminologies used in the industry in “just-in-time” manner due to the dynamism of the field itself. In view of this scenario, the present research seeks to shed some light using a workable model for developing a purposeful mobile Islamic banking terminology glossary app in a more convenient way and made it operational via devices such as iPhone, iPad or any Android-based smart gadgets. It further explored the prototype development and its implementations for mobile accessibility by providing multilingual glossary of Islamic banking and finance terminologies (Malay-Arabic-English).